logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Ad
0 votes

(n+2) = 60(n-1)

Can you answer this question?
 
 

1 Answer

0 votes
Given $ (n+2) = 60 (n-1)$
$\Rightarrow n + 2 = 60 n - 60$
$\Rightarrow n - 60 n = -2 - 60$
$\Rightarrow -59n = -62$
$\Rightarrow n = \large \frac{62}{59}$
Solution: $n = \large \frac{62}{59}$

 

answered Jun 4, 2013 by balaji.thirumalai
 

Related questions

+1 vote
1 answer
Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...